Human Resource Management Strategies for Enhancing the Competitiveness of Service Sector, Micro, Small and Medium Enterprises (MSME’s) in Manado City - Selvy R. Kalele; Alfian R. Poluan; Arifmanuel Kolondam (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Service-sector micro, small, and medium enterprises (MSMEs) play a vital role in regional economic development; however, many continue to face challenges in maintaining competitiveness due to limited human resource management (HRM) capabilities, inadequate workforce development, and resource constraints. Understanding context-specific HRM strategies is therefore essential to strengthen the competitiveness and sustainability of service-sector MSMEs Objective: This study aims to analyse human resource management (HRM) strategies for enhancing the competitiveness of service-sector micro, small, and medium enterprises (MSMEs) in Manado City. Methods: A qualitative approach with a multiple case study design was employed. Data were collected through in-depth interviews, non-participant observations, and documentation involving 16 informants, including business owners, managers, senior employees, and MSME support stakeholders. Data analysis was conducted using thematic analysis to identify key themes related to HRM practices, the role of HRM in improving competitiveness, and factors supporting or constraining its implementation. Results: The findings indicate that HRM strategies in service-sector MSMEs are contextual and adaptive, emphasizing relationship-based recruitment, on-the-job learning for competency development, and participative leadership by business owners. These strategies contribute to the development of employee capabilities, including service competence, loyalty, and work commitment, which serve as critical foundations for MSME competitiveness. However, limited resources and restricted access to formal training remain significant challenges in optimizing the strategic role of HRM. Conclusion: This study contributes to the enrichment of the strategic HRM literature by providing context-based insights from service-sector MSMEs in emerging regional economies.